Mitochondrial calcium uniporter-mediated inhibition of 1-methyl-4-phenylpyridinium ions neurotoxicity in PC12 cells. Issue 7 (2nd May 2018) - Wang, Huiling; Zhao, Menglan; Chen, Jialong; Ren, Yixian; Wang, Guanghai; Li, Wenjun; Zou, Fei
Abstract : Parkinson's disease (PD) is one of the most debilitating neurodegenerative disorders. The etiology of sporadic PD remains unknown. One prominent hypothesis is that impaired mitochondrial function may underlie slow and progressive neurodegeneration. Mitochondrial calcium uniporter (MCU) is a crucial component that regulates the intramitochondrial Ca 2+ level. Ca 2+ uptake to the mitochondria by MCU, resulting in activation of mitochondrial dehydrogenases and stimulation of ATP synthesis, but excessive Ca 2+ uptake to the mitochondria resulting in cell apoptosis. Therefore, this study focused on whether MCU was involved in the apoptosis induced by 1-methyl-4-phenylpyridinium ions (MPP + ) in PC12 cells. Our results showed that the viability of PC12 cells was inhibited by MPP + in a concentration-dependent and time-dependent manner. The expression of MCU was decreased gradually with a certain concentration of MPP + . Meanwhile, MPP + decreased the mitochondrial transmembrane potential and increased the apoptosis in PC12 cells. Notably, preincubated with Spermine, an MCU-specific agonist, or exogenously expressed MCU significantly alleviated cell apoptosis and decreased the reactive oxygen species production in PC12 cells that is induced by MPP + treatment. Knockdown of endogenous MCU expression or preincubation with a specific inhibitor of MCU enhances the cell apoptosis and the reactive oxygen species in PC12. Thus, MCU is involved in the apoptosis in PC12 induced by MPP + .